Survival of acetic acid bacteria in tuba subjected to different pasteurization temperatures - Orbeta, Jan Adrian B
The present study experimentally investigated the effects of temperature and pasteurization time on the survival of acetic acid bacteria (AAB) in tuba. Tuba was pasteurized at temperatures of 52° C, 54° C, 56° C, 58° C, 60° C, and 62° C for I minute to I 0 minutes at I minute intervals. Afterwards, pasteurized tuba were aseptically plated onto an Acetic Acid-Ethanol Medium and incubated at 37° C for 48 hours to facilitate microbial growth. Results revealed that the AAB population in tuba is significantly reduced by pasteurization even at the lowest temperature of 52° C and shortest process time of 1 minute. Furthermore, results showed that the AAB population was generally reduced as both pasteurization temperature and time were increased. This is reflected by the descending D-values of 18.48 minutes, 17.92 minutes, 15.75 minutes, 13.30 minutes, 11.72 minutes, and I 0.42 minutes as the pasteurization temperature increased from 52° C to 62° C. The Z-value was calculated to be a relatively high 37.45° C. This thermal resistance can be attributed to the presence of environmental stresses during fermentation, thermotolerant bacterial strains in composition, and the presence of oils and fats, proteins, and sugars in tuba, which essentially serve as protective barriers against heat. Despite the relatively high thermal resistance of the target microorganism, pasteurization was found to be effective in reducing the number of AAB in tuba. It is a cheap and accessible preservation method that is suitable even for the traditional mananggiti in the rural areas of the Philippines. Among the parameters, HTST pasteurization of tuba is preferred as it is more effective against thermally resistant AABs, requires less overall energy, and helps retain more bioactive compounds compared to L TL T pasteurization.